Impact of Hysteresis Curve on Subthreshold Swing in Ferroelectric FET - Jung, Hakkee (Vietnam Journal of Science and Technology, 2024)
The changes in Subthreshold Swing (SS) were observed for changes in remanent polarization Pr and coercive field Ec, which determine the characteristics of the P-E hysteresis curve of ferroelectric in Ferrolectric FET (FeFET). A multilayer structure of Metal-Ferroelectric-Metal-Insulator-Semiconductor (MFMIS) was used for the junctionless double gate structure. To obtain the SS value, the analytical SS model was used. The ranges of 15≤Pr ≤30 μC/cm2 and 0.8≤Ec≤1.5 MV/cm, which were reasonable in various experiments and did not generate unstable regions in the relationship of drain current and gate voltage, were considered. As a result, the SS decreased as Pr decreased and Ec increased due to the capacitance change in the ferroelectric. This phenomenon is because the controllability of channel carriers by the gate voltage increases due to the increasing of change in the ferroelectric voltage for the gate voltage as Pr decreases and the memory window increases. Since the SS decreased linearly in the memory window, the SS constantly changed according to the ratio of Pr and Ec, Pr/Ec. As the ferroelectric thickness increased, the SS decreased significantly, but the change of SS with respect to the Pr/Ec was severe. In general, as the channel length decreases, SS increases. However, when the Pr/Ec decreased to 10 pF/cm, the SS tended to decrease as the channel length decreased. The reason for this can be attributed to the fact that the relative thickness of ferroelectric increases with small channel length.